Effective teaching in gifted education : using a whole school approach - Robinson, Wendy, 1968- (Routledge/Taylor & Francis, 2010)
Effective teaching for gifted and talented students is high on the agenda of school systems across the world. This title presents an analysis of the practice of schools judged to be outstanding in their effective teaching of gifted and talented students.